1997
DOI: 10.1074/jbc.272.24.15496
|View full text |Cite
|
Sign up to set email alerts
|

Specific, High Affinity Binding of Tissue Inhibitor of Metalloproteinases-4 (TIMP-4) to the COOH-terminal Hemopexin-like Domain of Human Gelatinase A

Abstract: The binding properties of the newly described tissue inhibitor of metalloproteinases-4 (TIMP-4) to progelatinase A and to the COOH-terminal hemopexin-like domain (C domain) of the enzyme were examined. We present evidence for the first time of a specific, high affinity interaction between TIMP-4 and the C domain of human gelatinase A and show that TIMP-4 binds both progelatinase A and the C domain in a similar manner to that of TIMP-2. Saturable binding of recombinant C domain to TIMP-4 and to TIMP-2 but not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
107
0
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(120 citation statements)
references
References 46 publications
6
107
0
7
Order By: Relevance
“…Binding of MMP-2 to TIMP-4 was of high affinity with an apparent K d of 1.7 ϫ 10 Ϫ7 M but sightly weaker than that to TIMP-2 (apparent K d of 6.6 ϫ 10 Ϫ8 M) (43). These K d differences are in agreement with the relatively more potent inhibitory effect of TIMP-2 on MMP-2 than that of TIMP-4 (Fig.…”
Section: Figsupporting
confidence: 76%
See 1 more Smart Citation
“…Binding of MMP-2 to TIMP-4 was of high affinity with an apparent K d of 1.7 ϫ 10 Ϫ7 M but sightly weaker than that to TIMP-2 (apparent K d of 6.6 ϫ 10 Ϫ8 M) (43). These K d differences are in agreement with the relatively more potent inhibitory effect of TIMP-2 on MMP-2 than that of TIMP-4 (Fig.…”
Section: Figsupporting
confidence: 76%
“…A more detailed structural comparison indicated that TIMP-4 shares a relatively high identity with TIMP-2 particularly in the loops of 4 and 5 within the Cterminal domain (41). Thus, it is possible that TIMP-4 and TIMP-2 may share similar mechanistic and functional properties based on the sequence identity, similar enzymatic kinetics, and the high affinity binding to MMP-2 (43).…”
Section: Figmentioning
confidence: 99%
“…These results suggest that the pericellular activity of MMP-2 is tightly regulated by membrane-bound TIMP-2 and surrounding extracellular matrix components. TIMP-4 and TIMP-3 can also bind to proMMP-2 with high a nity (Butler et al, 1999;Bigg et al, 1997), but do not promote MT1-MMP mediated activation of proMMP-2 (Hernandez- Barrantes et al, 2001).…”
Section: Paradox 2: Timps Regulate Pro-mmp Activation and Tumor Angiomentioning
confidence: 99%
“…The zymogenic forms of both enzymes interact, via their C-terminal domain (hemopexin-like domain), with tissue inhibitors of metalloproteinases (TIMPs), a family of specific endogenous MMP inhibitors (15,16). Pro-MMP-9 binds to TIMP-1 (1), whereas pro-MMP-2 binds to TIMP-2 (17) and to TIMP-4 (18). After activation, any TIMP molecule efficiently inhibits the enzymatic activity by binding to the catalytic domain of the MMP (16).…”
mentioning
confidence: 99%